The role of motivation and emotions in physical education: understanding academic achievement and the intention to be physically active - Fierro-Suero, Sebastián; Castillo, Isabel; Almagro, Bartolomé J.; Saénz-López, Pedro (Frontiers in Psychology, 2023)
This study aims to understand how emotions and motivation influence the academic achievement of physical education (PE) students and their future intention to practice physical activity (PA). Despite the influence on student's behaviors and the reciprocal associations between motivation and emotion, the number of studies addressing both constructs at the same level is very limited. A structural equation model was used with 799 students aged 11 to 17 years (M = 13.16; SD = 1.17). The results showed that the teacher support of the basic psychological needs (BPN) predicted students' BPN satisfaction, which in turn predicted their autonomous motivation and positive emotions, and negatively predicted their negative emotions. Finally, autonomous motivation predicted students' intention to be physically active, whereas academic achievement was predicted by both autonomous motivation and emotions. We conclude that to better understand the consequences of PE classes, it is necessary to consider both constructs.